A Method for Mounting Space Telescope Optical Systems Based on the Sensitivity Matrix of Intrinsic Coefficients - Han Hou; Hongchang Ding; Keyan Dong; Guohua Cao; Boyuan Wang (Sensors)
Aperture space telescopes are widely used in space debris size information detection and celestial body detection work. For the problem of limited space inside the optical system of large aperture telescopes, a space telescope mounting method based on the intrinsic coefficient sensitivity matrix is proposed by combining the wavefront detection technology. Compared with the traditional sensitivity matrix method, the method in this paper does not need to partition the detector and simplifies the construction of the wavefront reconstruction matrix. Characterisation of the system wave aberration is realised by using the eigenfactors, and the sensitivity matrix model is established according to the amount of misalignment. The experimental tests are carried out on the telescope with a diameter of 1.2 m, and the results show that the root mean square (RMS) values of the wavefront aberration in the centre field of view are less than <semantics>λ/16</semantics> under the cases of eccentricity misalignment of the sub-mirror and tilting misalignment with the phase-aberration correction, which is of good value for the mounting of space telescope optical systems.